STRATEGI IMPLEMENTATION OF TOTAL QUALITY MANAGEMENT IN EDUCATION INSTITUTIONS - Yasnimar Ilyas (Journal Of Educational Experts (JEE), 2019)
In education sector, Total Quality Management is philosophy about sustainable improvement, that is contribute a practice tool to each educational institution to cover needs, wills and hopes of consumer’s satisfaction. The main word wich is involved with Total Quality Management is continous improvement and quality improvement. Total Quality Management is one of management strategy to response external challenges to cover consumer’s satisfaction.Fundamental; Total Quality Management consist of two basic aspect:1.                               Quality Manajemen System-QMS2.                               Continous Quality Improvement-CQIIn case to make implementation management concept, the strategy which is able to implement by education institution is evaluation to analyze strongness and weekness. Based on that evaluation, the educational institution and all it’s stakeholder consider and formulate quality target.The next step is to adjust planning including cost that refers to priority scale and national policy and depend on condition and resources each educational institution. In arranging program, the educational institution must define indicators or quality target. The most important step is monitoring and final evaluation. In monitoring, implementation of program is compared with the quality target defined before and also with the cost planning. The result of this evaluation can be used to adjust planning in the future. This process is a sustainable process.